Faktor-faktor yang Mempengaruhi Mutu Program Bimbingan dan Konseling di Sekolah - Herlina, Uray; Yusuf, Syamsu; Ahman, Ahman; Ilfiandra, Ilfiandra (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This study aims to describe what factors influence the quality of the Guidance and Counseling program at the junior high school (SMP) level in Pontianak city. This study uses qualitative research methods with interview techniques as the primary tool. In addition to that, observation is carried out as a research support tool. The selection of the sample in the study used purposeful sampling. In this case, the participants in the study were School counselors who are members of the School Counselor Deliberations (MGBK) for junior high schools in Pontianak City and already have educator certificates as professional School Counselors. Data analysis was conducted qualitatively through data reduction, data display, and conclusion. The study's results concluded that two factors influenced the quality of the Guidance and Counseling program at the Pontianak City Junior High School (SMP) level. The first was internal factors, including; educational background, work experience, work motivation, and competence in managing the Guidance and Counseling program. While the second is external factors, namely leadership support, facilities and infrastructure, and cooperation with other parties.